Leaking stoppage slurry for low-density window stratum as well as preparation method and application of leaking stoppage slurry
By using modified fibers and specific fill materials in the plugging slurry, the problem of excessive amount of solid phase particles in the drilling of low-density window formations is solved, and better plugging effect and stability are achieved.
Patent Information
- Application Number
- CN202311249254.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the drilling process of low-density window formations, excessive amount of solid phase particles in the existing leak-blocking slurry, resulting in the re-fracture of the well wall, making the leakage more serious, making it difficult to effectively plug the leakage.
Modified fibers are used as the bridging material, and prepared by reacting with ferric chloride, 8-hydroxyquinoline, ferric chloride powder and nano-calcium carbonate to form modified fibers loaded with iron complexes, reducing the amount of solid phase particles, and using them in combination with gel ZND-2 and nanobarite powder to improve the leakage plugging effect.
It effectively reduces the amount of solid phase particles in the leak-blocking slurry, enhances the leak-blocking effect, can better prevent solid phase particles from being lost in the low-density window formation, and improves the stability and effect of leak-blocking.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of drilling fluid, and specifically relates to a plugging slurry for low-density window formations. The invention also relates to a preparation method and application of the plugging slurry, and also relates to a preparation method of modified fibers in the plugging slurry. Background Art
[0002] The drilling fluid density window refers to the range of drilling fluid density that can maintain downhole pressure balance while not causing drilling complications such as leakage, blowout, sticking, and collapse during the drilling of oil and gas wells. The low-density window refers to a narrow range of drilling fluid density, which is mainly manifested as two lows and two highs, namely, the formation loss pressure is too low, the formation fracture pressure is too low, and the formation pore pressure is too high, and the formation collapse pressure is too high. For formations with low drilling fluid density windows, when leakage occurs, the density of the plugging slurry used cannot be too high, otherwise the well wall will be fractured again, causing more serious leakage. Currently, commonly used plugging slurries usually use a large number of various solid phase particles such as barite, calcium carbonate, shell powder, walnut shell powder, etc. to fill the cracks in the well wall to achieve the purpose of plugging.
[0003] However, in the plugging process, as the amount of solid particles increases, the density of the plugging slurry increases, causing the well wall to be fractured again, and the leakage becomes more serious. Therefore, it is urgent to design a plugging slurry with less solid particles and good plugging effect. Summary of the invention
[0004] The first object of the present invention is to provide a plugging slurry for low-density window formations, which has the effect of reducing the amount of solid particles added in the plugging slurry.
[0005] The second object of the present invention is to provide a method for preparing modified fibers in plugging slurry for low-density window formations.
[0006] The third object of the present invention is to provide a method for preparing a plugging slurry for low-density window formations.
[0007] The fourth object of the present invention is the application of plugging slurry for low-density window formations.
[0008] The first technical solution adopted by the present invention is that the plugging slurry for low-density window formations is composed of the following raw materials in parts by weight: 100 parts by weight of water, 30-40 parts by weight of gel, 10-14 parts by weight of bridging material, and 12-14 parts by weight of filling material.
[0009] The first technical solution of the present invention is also characterized in that:
[0010] The gel used was ZND-2.
[0011] The filling material is nano-baryte powder, and the particle size of the nano-baryte powder is 5μm-8μm.
[0012] The bridging material is modified fiber.
[0013] The second technical solution adopted by the present invention is a method for preparing modified fibers in a plugging slurry for low-density window formations, which is specifically implemented according to the following steps:
[0014] Step 1, soaking the fiber and the ferric chloride solution in a high-pressure reactor to obtain the iron-containing fiber;
[0015] Step 2, washing and drying the iron-containing fiber in step 1, and placing the fiber in a three-necked flask, and adding deionized water into the three-necked flask to obtain a first mixture;
[0016] Step 3, adding hydrochloric acid solution to the first mixture in step 2, and adjusting the pH value to 3-5 to obtain a second mixture;
[0017] Step 4, adding 8-hydroxyquinoline, ferric chloride powder and nano calcium carbonate to the second mixture in step 3, heating and stirring, the heating temperature is 60-80° C., and the stirring time is 20-30 minutes to obtain a third mixture;
[0018] Step 5: centrifuge, wash and dry the third mixture in step 4 to obtain modified fiber.
[0019] The second technical solution of the present invention is also characterized in that:
[0020] The immersion pressure in step 1 is 1.2MPa-1.5MPa, the immersion temperature is 40°C-60°C, and the immersion time is 22h-24h.
[0021] The mass ratio of the iron-containing fiber, 8-hydroxyquinoline, ferric chloride powder and nano-calcium carbonate in the third mixture in step 4 is: iron-containing fiber: 8-hydroxyquinoline: ferric chloride powder: nano-calcium carbonate = 1: (0.1-0.3): (0.5-0.7): (0.5-0.7).
[0022] The third technical solution adopted by the present invention is a method for preparing a plugging slurry for a low-density window formation, and the specific steps are as follows:
[0023] Step 1, according to weight parts, take 100 weight parts of water, 30-40 weight parts of gel, 10-14 weight parts of bridging material, and 12-14 weight parts of filling material;
[0024] Step 2: Add gel, bridging material and filling material to water in sequence under stirring.
[0025] The fourth technical solution adopted by the present invention is the application of the plugging slurry for low-density window formations in the first technical solution in the drilling plugging construction of low-density windows.
[0026] The beneficial effects of the present invention are:
[0027] The invention discloses a plugging slurry for low-density window formations. The plugging slurry reduces the amount of solid phase particles in the plugging slurry and enhances the plugging effect of the plugging slurry by adding modified fibers as bridging materials.
[0028] The invention discloses a method for preparing modified fibers in a plugging slurry for low-density window formations. By this method, 8-hydroxyquinoline is complexed with Fe3+ in ferric chloride, so that the surface of the modified fibers is uneven, the gripping force of the modified fibers is enhanced, and the modified fibers can better capture entangled solid particles.
[0029] The method for preparing the plugging slurry for low-density window formations of the present invention only requires sequentially adding gel, bridging material and filling material into water under a stirring environment, which is convenient to operate and saves preparation costs. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with specific implementation modes.
[0031] The first technical solution of the present invention is to provide a plugging slurry for low-density window formations, which is composed of the following raw materials in parts by weight: 100 parts by weight of water, 30-40 parts by weight of gel, 10-14 parts by weight of bridging material, and 12-14 parts by weight of filling material.
[0032] The gel adopts gel ZND-2, and the viscosity of the plugging slurry can be effectively improved by adopting gel ZND-2.
[0033] The filling material is micro-baryte powder, and the particle size of the micro-baryte powder is 5μm-8μm. The role of the barite powder is that when the bridging material is fiber, the fibers are entangled with each other to construct a three-dimensional space structure. There are many gaps in the space structure, and the micro-baryte powder can fill these gaps.
[0034] The bridging material adopts modified fiber, wherein adding the modified fiber as the bridging material reduces the amount of solid phase particles added in the plugging slurry, thereby enhancing the plugging effect of the plugging slurry.
[0035] The second technical solution of the present invention is to provide a method for preparing modified fibers in a plugging slurry for a low-density window formation, which is specifically implemented according to the following steps:
[0036] Step 1, soaking the fiber and the ferric chloride solution in a high-pressure reactor to obtain the iron-containing fiber;
[0037] Step 2, washing and drying the iron-containing fiber in step 1, and placing the fiber in a three-necked flask, and adding deionized water into the three-necked flask to obtain a first mixture;
[0038] Step 3, adding hydrochloric acid solution to the first mixture in step 2, and adjusting the pH value to 3-5 to obtain a second mixture;
[0039] Step 4, adding 8-hydroxyquinoline, ferric chloride powder and nano calcium carbonate to the second mixture in step 3, heating and stirring, the heating temperature is 60-80° C., and the stirring time is 20-30 minutes to obtain a third mixture;
[0040] Step 5: centrifuge, wash and dry the third mixture in step 4 to obtain modified fiber.
[0041] The soaking pressure in step 1 is 1.2MPa-1.5MPa, the soaking temperature is 40℃-60℃, the soaking time is 22h-24h, and the pressure is selected to be 1.2MPa-1.5MPa. The purpose is that the iron ions can be better adsorbed on the fiber surface under the pressure environment, thereby achieving better soaking effect.
[0042] Step 4: The mass ratio of the iron-containing fiber, 8-hydroxyquinoline, ferric chloride powder and nano-calcium carbonate in the third mixing is: iron-containing fiber: 8-hydroxyquinoline: ferric chloride powder: nano-calcium carbonate = 1: (0.1-0.3): (0.5-0.7): (0.5-0.7).
[0043] The modified material fiber prepared by the above method is loaded with a large amount of iron complex, that is, 8-hydroxyquinoline is complexed with Fe3+ in ferric chloride, which makes the surface of the modified fiber uneven, enhances the grip of the modified fiber, and enables the modified fiber to better capture the entangled solid particles, so that a large amount of solid particles in the plugging slurry can be effectively prevented from being lost from the cracks to the formation, thereby reducing the amount of solid particles added in the plugging slurry and enhancing the plugging effect of the plugging slurry.
[0044] The third technical solution of the present invention is to provide a method for preparing a plugging slurry for a low-density window formation, and the specific steps are as follows:
[0045] Step 1, according to weight parts, take 100 weight parts of water, 30-40 weight parts of gel, 10-14 weight parts of bridging material, and 12-14 weight parts of filling material;
[0046] Step 2: Add gel, bridging material and filling material to water in sequence under stirring.
[0047] The above method is easy to implement and saves preparation costs.
[0048] The fourth technical solution of the present invention is to apply the plugging slurry for low-density window formations in the plugging construction of low-density windows during drilling. The amount of solid phase particles added during the use of the plugging slurry for low-density window formations is reduced, and the plugging effect of the plugging slurry is better.
[0049] The preparation method of the modified fiber of the present invention, the specific embodiment is as follows:
[0050] Example 1
[0051] This embodiment 1 is used to prepare modified fibers, and the specific preparation method is as follows:
[0052] S1, placing the fiber and the ferric chloride solution in a high-pressure reactor and soaking them at a pressure of 1.4 MPa, a soaking temperature of 50° C., and a soaking time of 23 hours to obtain iron-containing fiber;
[0053] S2, washing and drying the iron-containing fibers, placing the fibers in a three-necked flask, and pouring deionized water into the three-necked flask to obtain a first mixture;
[0054] S3, adding hydrochloric acid solution to the first mixture, adjusting the pH value to 4, and obtaining a second mixture;
[0055] S4, adding 8-hydroxyquinoline, ferric chloride powder and nano-calcium carbonate to the second mixture, in a mass ratio of fiber, 8-hydroxyquinoline, ferric chloride powder and nano-calcium carbonate = 1:0.2:0.6:0.6, heating and stirring, the heating temperature is 70° C., and the stirring time is 25 minutes to obtain a third mixture;
[0056] S5. Centrifuge, wash and dry the third mixture to obtain modified fiber G1.
[0057] Example 2
[0058] This embodiment 2 is used to prepare modified fibers, and the preparation method is as follows:
[0059] S1, placing the fiber and the ferric chloride solution in a high-pressure reactor and soaking them at a pressure of 1.2 MPa, a soaking temperature of 40° C., and a soaking time of 22 hours to obtain iron-containing fiber;
[0060] S2, washing and drying the iron-containing fibers, placing the fibers in a three-necked flask, and pouring deionized water into the three-necked flask to obtain a first mixture;
[0061] S3, adding hydrochloric acid solution to the first mixture, adjusting the pH value to 3, and obtaining a second mixture;
[0062] S4, adding 8-hydroxyquinoline, ferric chloride powder and nano-calcium carbonate to the second mixture, in a mass ratio of fiber: 8-hydroxyquinoline: ferric chloride powder: nano-calcium carbonate = 1:0.1:0.5:0.5, heating and stirring, the heating temperature is 60° C., and the stirring time is 20 minutes, to obtain a third mixture;
[0063] S5. Centrifuge, wash and dry the third mixture to obtain modified fiber G2.
[0064] Example 3
[0065] This embodiment 3 is used to prepare modified fibers, and the preparation method is as follows:
[0066] S1, placing the fiber and the ferric chloride solution in a high-pressure reactor and soaking them at a pressure of 1.5 MPa, a soaking temperature of 60° C., and a soaking time of 24 hours to obtain iron-containing fiber;
[0067] S2, washing and drying the iron-containing fibers, placing the fibers in a three-necked flask, and pouring deionized water into the three-necked flask to obtain a first mixture;
[0068] S3, adding hydrochloric acid solution to the first mixture, adjusting the pH value to 5, and obtaining a second mixture;
[0069] S4, adding 8-hydroxyquinoline, ferric chloride powder and nano-calcium carbonate to the second mixture, in a mass ratio of fiber: 8-hydroxyquinoline: ferric chloride powder: nano-calcium carbonate = 1: 0.3: 0.7: 0.7, heating and stirring at a heating temperature of 80° C. for 30 minutes to obtain a third mixture;
[0070] S5. Centrifuge, wash and dry the third mixture to obtain modified fiber G3.
[0071] The plugging slurry for low-density window formation of the present invention has the following specific embodiments:
[0072] Example 4
[0073] This embodiment 4 is used to prepare plugging slurry for low-density window formations, and the specific preparation method is as follows:
[0074] Under stirring conditions, 35 parts by weight of gel ZND-2, 12 parts by weight of modified fiber G1 and 13 parts by weight of nano-baryte powder with a particle size of 7 μm were added to 100 parts by weight of water in turn to obtain plugging slurry A1 for low-density window formations.
[0075] Example 5
[0076] The remaining features are the same as those of Example 4, except that the modified fiber uses G2 in Preparation Example 2, and finally the plugging slurry A2 for low-density window formations is obtained.
[0077] Example 6
[0078] The remaining features are the same as those of Example 4, except that the modified fiber is G3 in Preparation Example 3, and finally the plugging slurry A2 for low-density window formations is obtained.
[0079] Comparative Example
[0080] The remaining features are the same as those of Example 4, except that ordinary unmodified fibers are used to obtain the plugging slurry D1.
[0081] The plugging slurries A1, A2, A3, and D1 prepared in the above-mentioned Examples 4, 5, 6, and Comparative Examples were respectively poured into a plugging tester, and a QD-2 plugging tester was used. The length of the seam plate of the QD-2 plugging tester was 30 mm and the width was 1 mm. The plugging performance test was performed, and the experimental results are as follows:
[0082] Table 1 Plugging performance test of plugging slurry
[0083] Experimental Group Pressure(MPa) A1 7 A2 7 A3 7 D1 2
[0084] It can be seen from the data in Table 1 that the plugging slurry D1 using ordinary fibers will break the plugging layer at the seam plate when the pressure is 2MPa, while the plugging slurries A1-A3 used for low-density window formations according to the present invention can withstand a pressure of 7MPa.
[0085] Therefore, the plugging slurry used for low-density window formations of the present invention adds modified fibers as bridging materials. Since the modified fibers are loaded with a large amount of iron complexes, namely, 8-hydroxyquinoline complexed with Fe3+ in ferric chloride, the surface of the modified fibers is uneven, which enhances the grip of the modified fibers and enables the modified fibers to better capture the entangled solid particles. This can effectively prevent a large amount of solid particles in the plugging slurry from being lost into the formation through the cracks, thereby reducing the amount of solid particles added in the plugging slurry and enhancing the plugging effect of the plugging slurry.
Claims
1. A plugging slurry for low-density window formations, characterized in that: The invention is composed of the following raw materials in parts by weight: 100 parts by weight of water, 30-40 parts by weight of gel, 10-14 parts by weight of bridging material and 12-14 parts by weight of filling material.
2. The plugging slurry for low-density window formation according to claim 1, characterized in that: The gel used is gel ZND-2.
3. The plugging slurry for low-density window formation according to claim 1, characterized in that: The filling material is nano-baryte powder, and the particle size of the nano-baryte powder is 5 μm-8 μm.
4. The plugging slurry for low-density window formation according to claim 1, characterized in that: The bridging material is modified fiber.
5. A method for preparing modified fibers in a plugging slurry for low-density window formations, characterized in that: The modified fiber is the modified fiber in claim 4, and is specifically implemented according to the following steps: Step 1, soaking the fiber and the ferric chloride solution in a high-pressure reactor to obtain the iron-containing fiber; Step 2, washing and drying the iron-containing fiber in step 1, and placing the fiber in a three-necked flask, and adding deionized water into the three-necked flask to obtain a first mixture; Step 3, adding hydrochloric acid solution to the first mixture in step 2, and adjusting the pH value to 3-5 to obtain a second mixture; Step 4, adding 8-hydroxyquinoline, ferric chloride powder and nano calcium carbonate to the second mixture in step 3, heating and stirring, the heating temperature is 60-80° C., and the stirring time is 20-30 minutes to obtain a third mixture; Step 5: centrifuge, wash and dry the third mixture in step 4 to obtain modified fiber.
6. The method for preparing modified fiber in plugging slurry for low-density window formation according to claim 5, characterized in that: The immersion pressure in step 1 is 1.2MPa-1.5MPa, the immersion temperature is 40°C-60°C, and the immersion time is 22h-24h.
7. The method for preparing modified fiber in plugging slurry for low-density window formation according to claim 6, characterized in that: The mass ratio of the iron-containing fiber, 8-hydroxyquinoline, ferric chloride powder and nano-calcium carbonate in the third mixture in step 4 is: iron-containing fiber: 8-hydroxyquinoline: ferric chloride powder: nano-calcium carbonate = 1: (0.1-0.3): (0.5-0.7): (0.5-0.7).
8. The method for preparing the plugging slurry for low-density window formation according to any one of claims 1 to 4, characterized in that: The specific steps are as follows: Step 1, according to weight parts, take 100 weight parts of water, 30-40 weight parts of gel, 10-14 weight parts of bridging material, and 12-14 weight parts of filling material; Step 2: Add gel, bridging material and filling material to water in sequence under stirring.
9. Use of the plugging slurry for low-density window formations as described in any one of claims 1 to 4 in drilling plugging construction of low-density windows.